Effect of a soccer ball`s surface texture on its aerodynamics and trajectory - Hong, S.; Goff, J. E.; Asai, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
The effect of a soccer ball`s surface texture on its aerodynamics and flight trajectory is not definitively known. For this study, five soccer balls were used, each having 32 panels with different surface textures. Their aerodynamics were examined via wind-tunnel experiments and then several non-spin trajectories were calculated for each ball. The results showed that the aerodynamic forces acting on a soccer ball change significantly depending on the surface texture of the ball, which in turn influences flight trajectories. The study contributes to an understanding of how a soccer ball`s surface influences the aerodynamics, which may impact the future design and development of soccer balls.